2019
DOI: 10.1007/s10961-019-09738-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge flows from public science to industrial technologies

Abstract: Scientific research has been acknowledged as an important knowledge resource for developing technologies. However, little is known about the heterogeneous nature of scientific knowledge and the associated contribution to technological advancement. Using nano technology as a case study, this paper investigates what types of scientific research can help improve the quality of technologies. This study uses backward and forward citation analysis, extracted from the Derwent World Patents Index. Non-patent citations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 50 publications
0
5
0
1
Order By: Relevance
“…Campbell and colleagues also found that the odds of research uptake in the patent literature was positively and significantly related to the multidisciplinarity of research teams on scientific papers, accounting for field of research and a number of additional variables (Campbell, Struck, Tippett, & Roberge, 2017). Wang and Li found similar results looking at the effect of the scope of integrated knowledge on uptake in patents (L. Wang & Li, 2018).…”
Section: Bibliometric Characterisation Of Xdr Research Practicesmentioning
confidence: 60%
“…Campbell and colleagues also found that the odds of research uptake in the patent literature was positively and significantly related to the multidisciplinarity of research teams on scientific papers, accounting for field of research and a number of additional variables (Campbell, Struck, Tippett, & Roberge, 2017). Wang and Li found similar results looking at the effect of the scope of integrated knowledge on uptake in patents (L. Wang & Li, 2018).…”
Section: Bibliometric Characterisation Of Xdr Research Practicesmentioning
confidence: 60%
“…The latter was defined as a process by which science and technology produced by public institutions in the peripheries (or semi-peripheries) is monetized in core countries, generally by companies that monopolize access to knowledge [ 5 , 29 , 30 ]. A way to measure knowledge extractivism is the identification of blind transfer of knowledge, i.e., the citation of scientific publications in patents where the former’s authors are not among patent co-owners and often are not even aware of the existence of such patents [ 31 , 32 ]. A concrete example of this form of knowledge extractivism concerns COVID-19 related papers.…”
Section: Discussionmentioning
confidence: 99%
“…The latter was defined as a process by which science and technology produced by public institutions in the peripheries (or semi-peripheries) is monetized in core countries, generally by companies that monopolize access to knowledge [8,30,31]. A way to measure knowledge extractivism is the identification of blind transfer of knowledge, i.e., the citation of scientific publications in patents where the former’s authors are not among patent co-owners and often are not even aware of the existence of such patents [32,33]. A concrete example of this form of knowledge extractivism concerns COVID-19 related papers.…”
Section: Discussionmentioning
confidence: 99%